MESI INITIATIVES IN TRAINING IN ICT IN EDUCATION AND EDUCATIONAL TECHNOLOGY - Maria A. Tatarinova (Открытое образование (Москва), 2016)
The article covers the context and development of higher education professional educational program for Applied Informatics in Education which was created to answer the challenges of new ICT rich educational environment. The program was initiated to train the specialists for emerging E-Learning sphere having integrated competences in Technology, Pedagogy and Management. The paper outlines the process of setting the educational program goals, building the trained specialists professional portrait, target audience, learning content selection and structuring, used educational technologies for training and future educational program development perspectives.